KOMUNIKASI ORGANISASI DALAM MANAJEMEN KONFLIK DI BEM SEKOLAH VOKASI IPB UNIVERSITY - Novi Karyanti; Suparman; Amiruddin Saleh; Rici Harpin Pranata; Nabhila Manisya; Khalila Zahra Maharani (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
This study examines the scope of communication in conflict management within the Student Executive Board (BEM) of the Vocational School at IPB University. Conflicts often arise in student organizations due to differing perspectives and work priorities. Effective organizational communication is essential for maintaining stability and achieving common goals. This study aims to analyze the organizational communication flow and communication strategies used by BEM SV IPB in conflict management. A qualitative method was employed, with data gathered through in-depth interviews with informants who are members of BEM SV IPB. The findings indicate that the Vocational School’s Student Executive Board at IPB University uses an open communication approach involving various structural levels in conflict management, from departmental/office daily board members to the general chairperson of BEM SV IPB. This approach allows conflicts to be resolved at the lowest level first, thus maintaining organizational effectiveness and strengthening the role of field coordinators. The organizational communication strategies implemented by BEM SV IPB in conflict management include regular meetings, formal and informal communication, as well as evaluations or feedback. This strategy is effective in easing tensions, maintaining relationships, and fostering a collaborative organizational communication culture. This study provides guidance and benefits for other student organizations in conflict management to enhance cooperation within the organization or group.